Senam Aisyiyah Bahagia: Gerakan Masyarakat Hidup Sehat di Kalangan Warga Aisyiyah Boyolali - Anisa Catur Wijayanti; Chayanita Sekar Wijaya; Widya Galih Puspita; Fairuz El Had; Muhammad Rivandi Athaya (Universitas Muhammadiyah Klaten, 2025)
NCDs can be a long-term burden for sufferers tend to be incurable, and can have a negative impact on all aspects of life. Problems owned by partners of the Institute of Arts and Sports (LBSO) for implementing health da'wah programs through Senam Aisyiyah Bahagia activities as a form of implementing physical activity to prevent and minimize the occurrence of NCDs. Implement and cultivate physical activity with Senam Aisyiyah Bahagia activities for Aisyiyah Boyolali Residents. Gymnastic exercises performed by members of Aisyiyah Regional Leadership. Senam Aisyiyah Bahagia activities can increase the physical activity of Aisyiyah Boyolali Residents. Senam Aisyiyah Bahagia activities are expected to increase the physical activity of Aisyiyah Boyolali residents, which can be implemented sustainably and cover a wider community